Rescue of self-reactive B cells by provision of T cell help in vivo - Cook, Matthew C (Eur J Immunol, 1998)
We have previously demonstrated that antigen-specific T cell help can rescue mature Ig transgenic (Tg) hen egg lysozyme (HEL)-specific B cells from tolerance induction upon transfer into soluble HEL-expressing Tg hosts. Here we extend these findings by showing that T cell help could also rescue both immature and mature self-reactive B cells from rapid deletion in response to high-avidity membrane-bound HEL. Moreover, although short-lived anergic peripheral B cells that had matured in the presence of soluble self antigen could not be rescued by provision of T cell help, a proportion of immature anergic IgM(+) IgD(−) CD23(−) B cells from the bone marrow of the same donors survived and proliferated when given help following transfer to a soluble or membrane HEL-expressing host. In other words, T cell help must be available relatively soon after the antigen signal to prevent induction of tolerance. Consistent with this interpretation, the stronger stimulus provided by membrane-bound antigen, which deletes immature B cells before they leave the bone marrow, did not afford an opportunity for T cell help to rescue tolerant immature bone marrow-derived B cells upon transfer in vivo. Nevertheless, these B cells were capable of responding to T cell help in vitro, which speaks against an immutable susceptibility of immature B cells to tolerance induction. Taken together, these data indicate that the strength of the antigen signal and availability of T cell help are the primary determinants of the fate of both immature and mature B cells, consistent with the model proposed by Bretscher and Cohn more than 25 years ago.